Efek Analgesik Ekstrak Batang Mentigi (Vaccinium varingiaefolium) dan Kandungannya - Ningsih, Indah Yulia; Zulfiah Nur Fajriani; Fransiska Maria Christianty; Ika Puspita Dewi; Ema Rachmawati (Faculty of Pharmacy, University of Jember, 2026)
Mentigi (Vaccinium varingiaefolium) is one of the herbal medicines used by the Tengger tribe in East Java, Indonesia, to treat pain. Several investigations have showed that the plant possesses analgesic substances, including anthocyanins. The objective of the study is to assess the analgesic effect of a 70% ethanolic extract from the stem of mentigi using the hot-plate test and acetic acid-induced writhing test. Additionally, the study aims to evaluate the chemical constituents of the extract using phytochemical screening. The findings indicated that the dose of 1200 mg/kg had the most significant analgesic effect, increasing the latency time (12.80±1.33 seconds), reducing the number of writhing (20.00±2.92), and increasing the percentage of analgesic power (65.75±5.07%). The effect is related to the chemical content of the extract, namely saponins, flavonoids, polyphenols and tannins. The study suggested that the stem extract of mentigi has the potential to be developed as an analgesic agent.